"Forget Me Not": Free Black Women and Sentimentality. (29th June 2015) - Cobb, Jasmine Nichole
Abstract : Friendship albums, blank volumes with decorative covers, emerged around 1825 as part of a growing market of women's print culture. Sentimentalism, the chief vocabulary of the friendship album genre, targeted white women consumers and largely ignored black women. However, freeborn African Americans rigorously engaged sentimental literature in the pages of the friendship album, recasting this artifact as a specimen of antebellum black print culture. This essay explores the production of African American friendship albums and examines artistic and literary contributions by freeborn black women writers.